Profil Komunikasi Matematis Siswa Tunanetra - Martina Retno; Nurmaningsih Nurmaningsih; Wandra Irvandi (Universitas Katolik Widya Karya Malang, 2023)
The research method used in this research is descriptive qualitative research with the aim of the research being to describe the mathematical communication profiles of blind students. This research was conducted at SLB Negeri Rasau Jaya which is located at Education Street No. 2, Desa Rasau Jaya Satu, Rasau Jaya District, Kubu Raya Regency, West Kalimantan Province, using the K13 curriculum. This study will describe the mathematical communication of SLBN Rasau Jaya students in the Cartesian coordinate material seen from aspects (1) The ability of students to give answers using everyday language in explaining ideas, situations and mathematical relations, orally or in writing with real objects, pictures, graphics and algebra. (Aspects of Written text); (2) Students' ability to connect real objects, pictures, and diagrams into mathematical ideas. (Drawing Aspects); (3) Students' ability to express everyday events in language or mathematical symbols. (Aspects of Mathematical Expression). In this study, the subjects of the study were all students of class VIII SLB Negei Rasau Jaya, which consisted of three students with low vision criteria. The data collection tools used in the research were observation sheets, interviews, and written tests. The mathematical communication skills of blind students have good abilities in the aspect of drawing. While the writing aspect was not fulfilled properly and the mathematical expression aspect did not meet the indicators at all.